Apical surgery failures: Extraction or re-surgery? Report of five cases - Damla Torul; Sevda Kurt; Kamber Kamberoglu (Tabriz University of Medical Sciences, 2018)
Apical surgery (AS) is considered as the last resort to save teeth which cannot be treated with a conventional endodontic approach. The main goal of apical surgery is to create a barrier between the root canal system and the peri-radicular tissues by means of a tight root-end filling after resection. However, failures in this treatment usually result in tooth loss. In such cases surgical re-treatment should be considered as a viable alternative. In this case series, successful ARs are presented that were performed on ten teeth in five patients referring for extraction after an unsuccessful apical surgery. It should be noted that if appropriate surgical and endodontic intervention is performed and adequate apical obturation is provided with retrograde filling, teeth can be treated without extraction.